Os usos políticos do passado: a transição democrática e o que resta da ditadura nos rastros da Revista Veja (1978-1985) - Gonçalves, Maxlander Dias (2021)
This thesis reviews the last eight years of the military dictatorship in Brazil with the object of the Letter to the reader, an editorial column of the magazine Veja, which seeks to recognize, in the democratic transition, the remains of the dictatorship. In the late 1970s, the dictatorship showed exhaustion. It was in this scenario where the barracks dispute took place, about the ideal moment for the departure of the military, raising the political temperature in the barracks and in society. Thus, the transition, between 1978 and 1985, occurred in the midst of a series of events that demonstrated to what extent the military were not willing to return the country to democratic normality if there was any danger to the project erected after the "Revolution". The sectors of society that supported the 1964 coup also debated the return of democracy, but feared the increase in popular discontent and setbacks among the Armed Forces. The magazine reproduced a speech on the transition, in proximity to the script planned by General Ernesto Geisel. He evoked the need for a policy of national conciliation, maintenance of social order, as well as a reordering of the Brazilian State under liberal principles. In its editorial – and based on a memory about the recent past –, the weekly tried, through memory, oblivion and silence, to weave a democratic rite without trembling, equalizing the power relations that were established at the time, removing the unwanted agendas and segments. In order to understand the ways in which Veja was involved in this transition process, the research proposed to present, on a first occasion, the role of the military in leading the dictatorship to its end amid the pressure from social movements for the immediate arrival of the democracy. In a second moment, based on the bibliographic debate, the work seeks to present the historiographic differences for the period, it seeks to debate the notion of political uses of the past and the form it assumes in the media. In a third and final part, the thesis follows in the footsteps of the journal, using the Content Analysis method. The traumatic experience of the recent Brazilian past – the “red threat” – appears in the weekly projectors of the military discourse on the democratic transition. We are interested in understanding where the consonances and oppositions are found as discursive forms assumed by Veja's editorials – regarding the path that the Armed Forces guided towards the end of the dictatorship – as popular pressure in defense of democracy grows.